RACIAL INJUSTICE IN THE HARPER LEE’S TO KILL A MOCKINGBIRD NOVEL: A MARXIST APPROACH - NOVITA, NOVITA (2011)
The research is proposed to analyze a racial injustice in Harper Lee’s To Kill A Mockingbird novel by Marxist Approach. There are two objectives: the first is to analyze the novel in term of structural elements, and the second is to analyze the novel based on the Marxist Perspective. The benefits of this study are to give in the application of Marxist Perspective in literary study and to fulfill the requirement for getting Bachelor Degree in English Department. This study is a qualitative study, using the novel of Harper Lee’s To Kill A Mockingbird as the object of analysis of the study There are two kinds of data sources: primary and secondary data. The primary data source is the text of the To Kill A Mockingbird novel itself, while the secondary data is taken from some books, articles, and other information needed. The method of data collection is library research by summarizing, paraphrasing, and documenting the data. The technique of data collection is descriptive. The outcome of the study shows that the novel illustrates a racial injustice and the condition of the Black people and White people in the early twentieth century. That is why Harper Lee criticizes that condition which is the reflection of her real childhood in 1930 in Southern State of America. S